Correction: Examining the U-shaped relationship between non-agricultural sources water pollution and the urban-rural income gap. - Dong He; Zhongyuan Sheng; Chunxiao Tian (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0305530.].